Web-Based Undergraduate Medical Education in a Virtual Learning Environment Using an Original Pedagogical Approach: an Observational Longitudinal Study - Magalhães,Lucas Vilas Bôas (2019)
ABSTRACT Background Asynchronous Web-based Medical Education in Virtual Learning Environments (VLEs) has grown steadily because of its many advantages. Various configurations and instructional methods are presently available. The existing proposals are poorly structured and/or not very effectively used for teaching diagnostic skills to undergraduate medical students in Brazil. A robust instructional method with positive pedagogical characteristics is needed. Thus, we have proposed a pedagogically-structured method for VLEs that includes a motivating initial reading (Medical Chronicle – MC), and a knowledge building program, using real cases coupled with audiovisual resources (Diagnostic Workshop – DW). We aimed to verify its acceptance, as well as the efficacy of the MC/DW method in improving the diagnostic ability of medical students, in the long term. Methods An opinion survey, two MC/DW materials and two Knowledge and Diagnostic Skills (KDS) questionnaires on stroke and epilepsy were developed, and two medical student groups were followed up in this 2013 longitudinal observational study. The students answered a KDS1, and attended a traditional lecture on one of the topics. They also accessed a VLE to apply the MC/DW method on stroke or epilepsy. We applied the same questionnaire (KDS2 and KDS3, respectively), one month and 5-6 months after the KDS1. We analyzed the mean KDS1 score of all the students, and the mean pairwise of those who accessed and those who did not access the VLEs during these three stages. An opinion survey was applied, and the results were analyzed by descriptive statistics. Results 87 students participated in the study, but six were excluded as they did not answer the questionnaires. The KDS1 general mean score was 1.59 (SD0.71). We found that 66 students (81.5%) accessed the VLE, showing a significant improvement in diagnostic skills in the KDS2 (mean5.65, p<0.05) and KDS3 (mean 4.57, p<0.05), with non-significant variations for those who did not access it. The MC was considered at least good for 62 students (94%), with 52 students (78.8%) finding that a checklist was sufficient to clear up all their DW doubts. Conclusions The MC/DW method in VLE proved to be effective for improving the diagnostic capability of the undergraduate medical students in the long term, and it was well accepted by the students. It presents several positive pedagogical characteristics and can be replicated.